Finite control‐set model predictive current control of five‐phase permanent‐magnet synchronous machine based on virtual voltage vectors. Issue 5 (1st May 2017) - Xue, Cheng; Song, Wensheng; Feng, Xiaoyun
Abstract : This study proposes a finite control‐set model predictive current control (FCS‐MPCC) scheme based on virtual voltage vectors for five‐phase permanent magnet synchronous machines, which aims to reduce the low‐order harmonic components of stator currents. In addition, comparing with traditional FCS‐MPCC algorithms, the proposed algorithm retains fast control dynamic response and brings several other benefits: such as smaller burden of calculation, approximate constant switching frequency in entire speed operation range and lower current harmonics, especially for three‐order harmonics. Furthermore, the one‐step delay compensate solution of the proposed FCS‐MPCC scheme in digital‐controller implementation is presented. Finally, a series of computer simulation and hardware‐in‐loop (HIL) experimental tests are adopted to compare the performances of the proposed FCS‐MPCC and two traditional FCS‐MPCC schemes. Simulation and HIL experimental results have verified the validity and effectiveness of the proposed FCS‐MPCC scheme using virtual voltage vectors.